Experimental and Numerical Investigation of the Geometrical Effect on Low Velocity Impact Behavior for Curved Composites with a Rubber Interlayer - Albayrak, Mustafa; Kaman, Mete Onur; Bozkurt, Ilyas (Springer, 2023)
The present study aims to produce sandwich composites with curved surfaces with different surface geometries by adding rubber (EPDM) between glass fiber woven fabrics and to examine their behavior under the influence of low-velocity impact numerically and experimentally. For this purpose, glass fiber and rubber layers were added to steel molds manufactured in curved forms and sandwich plates were produced through the vacuum infusion method. Low-velocity impact tests were performed by lowering strikers with a hemispherical tip on the produced curved-surface plates, and the effect of the surface geometry on the impact energy absorption was determined. By using rubber intermediate layers, the energy absorption ability can be increased by a maximum of 21%. The curved surface geometry affects the absorbed energy. If the height of the curved surface composites is kept constant and the width is increased to 1.5 times, the impact energy absorption increases by 16 percent. If the width is kept constant and the height is increased to 2.3 times, the impact energy absorption has decreased by 13 percent. When the impact resistance of composites with triangular rectangular, R125 circular arc and flat geometries with the same height and width are compared, it is observed that the lowest impact absorption ability occurs in the plates with triangular geometry, while the impact damping feature increases as the surface geometry becomes flatter and accordingly the contact surface increases. The impact absorption energies of the specimens were determined to be 82% compared to the flat plates. When the impact absorption energies of the upper side lengths of the outer tangent quadrilaterals to the R125 circle arc are compared, a significant increase in the impact absorption capabilities was observed as the side lengths increased. In the numerical part, the tests performed were modeled using the LS-DYNA finite element package program and the Hashin damage criterion-based MAT162 material model was used in order to see the damage caused to the composite structure in three dimensions after the tests. The numerical results obtained were a minimum of 84% compatible to the experimental results.
Keywords: Curved composites; Rubber layer; Progressive failure analysis; Low velocity impact